Pemanfaatan Kecerdasan Buatan dalam Transformasi Pendidikan Sekolah Minggu Buddha Vihara Shimakalingga Jepara di Era Digital - Indika Siri (Jurnal Budi Pekerti Agama Buddha, 2025)
This study aims to examine the use of artificial intelligence (AI) in transforming Buddhist Sunday School education at the Shimakalingga Temple in Jepara in the digital era. Using a qualitative descriptive approach, data were collected through observation, interviews, and documentation studies. The results show that AI technology is beginning to be utilized in the learning process, such as the use of interactive visual media, Dharma quiz applications, and digital platforms for distance learning. The use of AI has been proven to increase student interest and understanding of Buddhist teachings, as well as support more inclusive and adaptive learning. However, challenges remain, including limited resources, lack of teacher training, and the need for ethical guidelines for the use of AI in the context of religious education. This study concludes that AI plays a significant role in supporting the transformation of Buddhist education, but its use must remain balanced with spiritual values and the role of teachers as moral guides. Therefore, collaboration between the temple, educators, and technology is needed to create a sustainable learning system based on Dharma values.